2014
DOI: 10.1038/mt.2014.41
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Murine Colitis and its Associated Cancer by Carcinoembryonic Antigen-Specific Regulatory T Cells

Abstract: The adoptive transfer of regulatory T cells (Tregs) offers a promising strategy to combat pathologies that are characterized by aberrant immune activation, including graft rejection and autoinflammatory diseases. Expression of a chimeric antigen receptor (CAR) gene in Tregs redirects them to the site of autoimmune activity, thereby increasing their suppressive efficiency while avoiding systemic immunosuppression. Since carcinoembryonic antigen (CEA) has been shown to be overexpressed in both human colitis and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
151
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 202 publications
(152 citation statements)
references
References 50 publications
0
151
0
1
Order By: Relevance
“…Similar differences in the ability to induce toxicities of T cells targeting CEA but expressing TCRs or CARs (Chimeric Antigen Receptor) were recently described by Magee and Snook (40). This and other studies also highlighted that the CEA expression level in the target organ is a key determinant in the development of toxicity and concluded that, similarly to CEA TCB antibody, CAR T cells can discriminate between cells with varying levels of antigen expression in vivo, providing a potential avenue to target antigens that are highly expressed by tumor cells but have lower expression in normal tissues (40,41).…”
Section: Discussionmentioning
confidence: 87%
“…Similar differences in the ability to induce toxicities of T cells targeting CEA but expressing TCRs or CARs (Chimeric Antigen Receptor) were recently described by Magee and Snook (40). This and other studies also highlighted that the CEA expression level in the target organ is a key determinant in the development of toxicity and concluded that, similarly to CEA TCB antibody, CAR T cells can discriminate between cells with varying levels of antigen expression in vivo, providing a potential avenue to target antigens that are highly expressed by tumor cells but have lower expression in normal tissues (40,41).…”
Section: Discussionmentioning
confidence: 87%
“…Transfer of regulatory T cells expressing a carcinoembryonic antigen-specific CAR lessens the severity of colitis in preclinical animal models. 54 Since pancreatic islet cells express B7-H4, investigation of B7-H4 CAR-bearing regulatory T cells could have therapeutic potential in Type-1 diabetes.…”
Section: Model To Interrogate Questions Addressing B7-h4's Function Amentioning
confidence: 99%
“…Recently, Tregs have also been investigated in clinical trials to prevent/treat T1D, graft-versushost diseases, and organ transplant rejection (16). Notably, it is well established in several models that Ag-specific Tregs are more effective than polyclonal Tregs in immunosuppression in vitro and control of autoimmunity in vivo (e.g., T1D, arthritis, multiple sclerosis, arthritis, colitis) (17)(18)(19)(20)(21)(22)(23)(24); particularly, injection of small numbers of Ag-specific Tregs selectively expanded in vitro can reverse diabetes even after disease onset (17,18). However, whether Ag-specific Tregs can be expanded in vivo, whether these cells retain their immunosuppressive function following expansion, and the stability of their Foxp3 expression have not yet been elucidated.…”
mentioning
confidence: 99%